Hyperhomocyst(e)inemia and endothelial dysfunction in IDDM - Hofmann Bowman, Marion; Kohl, Brigitte; Klevesath, Martina; Borcea, Valentin; Bierhaus, Angelika; Henkels, Mechthild; Amiral, Jean; Fiehn, Walter; Ziegler, Reinhard; Wahl, Peter; Nawroth, Peter Paul (Diabetes care, 1997)
While elevated blood levels of homocyst(e)ine represent an independent risk factor for macrovascular disease, we assessed the link between hyperhomocyst(e)inemia and diabetic microvascular diseases.Plasma levels of homocyst(e)ine and thrombomodulin (TM), markers of endothelial cell damage, were measured before and 3 h after oral methionine loading in 75 patients with IDDM and 40 healthy control subjects matched for sex and age. Exclusion criteria were hyperlipidemia, hypertension, smoking, or positive family history for cardiovascular disease.IDDM patients had higher pre- and postload plasma levels of homocyst(e)ine than did healthy control subjects (12.0 vs. 7.7 μmol/l and 27.6 vs. 16.0 μmol/l; P < 0.001). Of 75 IDDM patients, 26 had plasma homocyst(e)ine levels above the normal range (means ± 2 SD of values obtained in the control group). These IDDM patients with hyperhomocyst(e)inemia had higher plasma TM levels (62.2 vs. 38.2 ng/ml, P < 0.001), higher albumin excretion rates (485 vs. 115 mg/l, P < 0.005), and a higher prevalence of late diabetic complications (nephropathy, 76 vs. 33% retinopathy, 69 vs. 51% neuropathy, 57 vs. 41% and macroangiopathy, 57 vs. 33%) compared with IDDM patients with normal plasma homocyst(e)ine. In vitro experiments with human umbilical vein cells showed an increased release of TM into the culture supernatant only when endothelial cells were pretreated with advanced glycation end product (AGE)-albumin before L-homocystine was added. A synergistic action of homocyst(e)ine and AGEs might contribute to vascular complications in patients with diabetes.Hyperhomocyst(e)inemia is common in nephropathic diabetic patients and may contribute to the enhanced morbidity and mortality from cardiovascular diseases characteristically observed in IDDM patients with diabetic nephropathy.